The Influence of BT21 Character Illustrations on Products on Fans’ Pragmatic Consumption Patterns - Amalia Firdausya Yunizar; Intan Prameswari (Gorga : Jurnal Seni Rupa, 2025)
This study aims to analyze and test the relationship between the application of BT21 character illustrations in a product and its effect on the pragmatic consumption patterns of fans. This study uses a quantitative approach. The sample collection technique used was Purposive Sampling with 284 respondents. The respondents' criteria were K-pop fan groups and not having bought products with BT21 characters at least once a year, with an age range of 16-35 years. Primary data was obtained through an online questionnaire (Google Form) and secondary data through structured interviews. The data obtained was analyzed using SPSS 25, and the hypothesis was tested by bootstrapping regression. The results showed that the illustration of the BT21 character on the product significantly affected the pragmatic consumption pattern among K-pop fans, namely in the ARMY and K-popers group (p < 0.05). However, the illustration of the BT21 character did not significantly affect the pragmatic consumption pattern in the 'Non K-popers' group (p > 0.05).